PENGARUH KESADARAN MEREK, KEPUASAN KONSUMEN DAN KEPERCAYAAN KONSUMEN ATAS MEREK TERHADAP PEMBELIAN ULANGTIKET PESAWAT FIREFLY DI BANDA ACEH - Ika Rahmadani; Tia Risky Ayunda (universitas teuku umar, 2017)
ABSTRAKThe aim of this research is to know the influence of brand awareness, consumer satisfaction andconsumer trust on brand toward the re-purchasing of Firefly airline ticket in Banda Aceh. This study took 99respondents of re-purchasing of FireFly airline tickets in Banda Aceh. This research was conducted at the SultanIskandar Muda airport in Banda Aceh. Data analysis method which used in this research is multiple linearregression. The research results showed that the variables Brand Awareness, consumer satisfaction andconsumer trust for brand have significant influence to the repurchasing of Firefly airline tickets in Banda Aceh.In the future, it is expected that the re-purchasing of Firefly airline tickets in Banda Aceh should be able tomaintain their brand awareness, consumer satisfaction and consumer trust for brand and to improve otherfactors which is capable to creating consent to the consumer so that the consumer wants to recommendate to theothers.Keywords: Brand awareness, Consumer trust for brand, Cunsumer satisfaction, Repurchasing